Pengaruh Good Corporate Governance dan Ukuran Perusahaan Terhadap Integritas Laporan Keuangan dengan Kualitas Audit Sebagai Pemoderasi - Nindi Saputri; Andy Dwi Bayu Bawono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to evaluate the impact of institutional ownership, the presence of independent commissioners, and company size on the integrity of financial statements in companies listed on the Indonesia Stock Exchange (IDX) during the period from 2019 to 2023, considering the role of audit quality as a moderating variable. The analysis results show that independent commissioners and company size have a significant and positive impact on the integrity of financial statements, while institutional ownership does not have a significant effect. In addition, audit quality was not proven to moderate the relationship between institutional ownership, independent commissioners, and company size on the integrity of financial statements. This study has limitations, such as the sample being limited to manufacturing companies and the use of conservatism as the sole proxy for measuring financial statement integrity. Future research is recommended to expand the sample, extend the research period, and incorporate other variables such as profitability, leverage, managerial ownership, or audit fees.